Peer victimization in children with attention-deficit/hyperactivity disorder - SABUNCUOĞLU, OSMAN TALAT (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: The purpose of this study is to compare the presence of bullying behavior (both being a bully and being a victim) in newly diagnosed, medication naive children with attention-deficit/hyperactivity disorder (ADHD) with those who have been on a regime of regular methylphenidate treatment for ADHD for at least the past two school terms. Methods: A total of 34 medication-naive children (mean age 10.3 +/- 1.81) and 30 children (10.5 +/- 1.83) who were between 8 and 16 years, were evaluated with Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime Version (K-SADS-PL) for diagnoses of ADHD and coexisting psychiatric disorders. Children completed the Revised Olweus Bully/Victim Questionnaire and their parents and teachers completed a form based on the same questionnaire to identify the bullying involvement of the children. Results: In self-report measures, 41.2% (n=14) of the newly diagnosed children were classified as victims and 8.8% (n=3) as bully/victims. In the treatment group, 22.6% (n=7) of the children were classified as victims, 6.5% (n=2) as bullies and 12.9% (n=4) as bully/victims. The difference in victimization rates between the two groups did not reach the statistically significant levels. Bullying involvement rates were lower than self-reports according to the parent and teacher-rated bullying questionnaires (13.8% and 3.1% respectively). 26.7% (n=8) of the parents and 50% (n=4) of the teachers reported a decrease in bullying involvement after methylphenidate treatment. Conclusion: Peer victimization should be a part of clinical examination in children with ADHD. In addition to medication use, school interventions aiming at reducing peer victimization is indicated in children with ADHD.
Keywords: attention deficit hyperactivity disorder; bullying; peer victimization; methylphenidate; child; adolescent; MIDDLE-SCHOOL-CHILDREN; SELF; PREVALENCE; STABILITY; TEACHER; AGE